Acupoint-catgut embedment combined with medication does not decrease interleukin-6 levels serum in patients with gastroesophageal reflux disease: a randomized controlled clinical trial (Medical Journal of Indonesia, 2019)
BACKGROUND Gastroesophageal reflux disease (GERD) is a pathological condition caused by the reflux of stomach contents into the esophagus. GERD is a multifactorial disorder with an increase in prevalence worldwide. Interleukin-6 (IL-6) is a proinflammatory cytokine that is commonly found in the esophageal mucosa of GERD patients and associated with esophageal motor disorders. Acupoint-catgut embedment has long been known as adjunctive therapy for GERD. This study was aimed to establish the effect of acupoint-catgut embedment combined with medication on the IL-6 serum levels of patients with GERD. METHODS This single-blind randomized controlled trial involved 40 GERD patients from the Gastroenterology Outpatient Clinic of Cipto Mangunkusumo Hospital that were randomly allocated to either catgut-embedding therapy plus medication or sham acupuncture with medication. Catgut-embedding therapy was given two times at CV12 (Zhongwan), ST36 (Zusanli), and BL21 (Weishu) every 15 days. Serum levels of IL-6 were measured by enzyme-linked immunosorbent assay as research output. RESULTS There were no significant differences in the baseline levels of proinflammatory (IL-6) mediators between the groups. After 1-month treatment, the median levels of IL-6 were statistically insignificant decreased in catgut-embedding therapy plus medication versus sham acupuncture with medication (0.15 versus -0.16 pg/ml, respectively; p = 0.14). CONCLUSIONS The results suggest that catgut-embedding therapy has not been proven to statistically influence the levels of IL-6 in patients with GERD.